Benchmarking deep transfer learning for imbalanced skin cancer classification: Integrating focal loss, explainable AI, and web deployment - Yazid Aufar; Muhammad Daffa Abiyyu Rahman; M. Fadli Ridhani (SHM Publisher, 2026)
Non-melanoma skin cancer (NMSC) classification faces challenges like severe data imbalance and the